Tindak Pidana Pembunuhan Berencana yang Didahului dengan Kekerasan (Studi Putusan Nomor : 150/Pid.B/2020/PN Jkt Utr.) - Arief Widyantoro (Peneliti.net, 2023)
Aggravation of sanctions against perpetrators of premeditated murder preceded by violence (Study of Decision Number: 150/Pid.B/2020/PN Jkt Utr) in imposing a sentence on the Defendant, the panel of judges was unfair even though they had first considered the aggravating and mitigating circumstances of the Defendant where the aggravating circumstances were that the defendant's actions caused the victim witness Victor Tambatjong to suffer injuries; the Defendant had been convicted; the Defendant had enjoyed the payment for the execution of the murder of the victim Victor Tambatjong and the mitigating circumstances were that the Defendant regretted and admitted his actions frankly in court. Therefore the Defendant was sentenced with due observance of Article 340 Jo. Article 53 Paragraph (1) Jo. Article 55 Paragraph (1) To 1 of the Criminal Code. and Law Number 8 of 1981 concerning Criminal Procedure. Therefore, the panel of judges stated that the Defendant Johanes Ronald Sebenan, mentioned above, has been proven legally and convincingly guilty of committing the crime of